Aspiration, inspiration, and illustration: Initiating debate on reflective practice writing - Knowles, Z.; Gilbourne, D. (The Sport Psychologist, 2010)
The present article contemplates the future of reflective practice in the domain of applied sport psychology and, in so doing, seeks to engender further critical debate and comment. More specifically, the discussion to follow revisits the topic of`reflective-levels` and builds a case for `critical reflection` as an aspiration for those engaged in pedagogy or applied sport psychology training regimens. Assumptions and commentators associated with critical social science (e.g., Habermas, 1974; Carr & Kemmis, 1986), action research (e.g., Carr & Kemmis, 1986; Leitch & Day, 2000), and critical reflection (e.g., Morgan, 2007) suggest a number of foundation points from which critical reflection might be better understood. Finally, writing about ones- self via the processes of critical reflection and through reflective practice more generally are briefly considered in cautionary terms (Bleakley, 2000; du Preez, 2008). Auto-ethnography in sport (Gilbourne, 2002; Stone, 2009) is finally proposed as one potential source of illustration and inspiration for reflective practitioners in terms of both content and style.